Factors influencing the parking demand of the park and ride facility at Putrajaya public transportation terminal - Syed Adnan, Sharifah Adibah Alyia; Kadar Hamsa, Abdul Azeez (2015)
The upsurge of the working population has contributed to the increase of travel demand into the city centre. This situation has led to traffic congestion on the major highways leading into and out of the city. Transportation Demand Management (TDM) strategy known as the “park and ride” scheme was introduced towards encouraging commuters to use public transport. The purpose of this paper is to examine the factors that influence the parking demand of the park and ride facility at Putrajaya Sentral. A questionnaire survey was administered targeting both multi-storey and surface parking users on weekday and weekend. The questionnaire consists of three sections, which are socioeconomic profile, travel characteristics and parking characteristics. The method of analysis such as cross tabulation, Mann-Whitney U-Test, and Principal Component Analysis were applied. The findings revealed that factors such as parking availability, parking convenience and safety were significant difference between multi-storey and surface parking.